Learning mathematics in two dimensions: a review and look ahead at teaching and learning early childhood mathematics with children’s literature - Flevares, Lucia M.; Schiff, Jamie R. (Frontiers in Psychology, 2014)
In the past 25 years an identifiable interest in using children’s literature in mathematics learning emerged (Clyne & Griffiths, 1991; Haury, 2001; Hellwig, Monroe, & Jacobs, 2000; Hong, 1996; Welchman-Tischler, 1992). We critically review the rationales given for the use of picture books in mathematics learning, with a special focus on geometry due to its underrepresentation in this body of literature and the need for greater focus on this topic. The benefits and effectiveness of using picture books for children’s mathematics learning and interest have been documented (Hong, 1996; O’Neill, Pearce & Pick, 2004; Young-Loveridge, 2004). For geometry, although much learning of shape ideas should be hands-on, two-dimensional figures are essential to develop children’s understanding of plane geometry. Books may effectively engage pre-literate children with plane shapes (Skoumpourdi & Mpakopoulou, 2011; van den Heuvel-Panhuizen & Van den Boogaard, 2008) and shapes as gestalt wholes or prototypes (Clements et al., 1999; Hannibal, 1999; van Hiele, 1986). We review several guidelines and evaluative criteria for book selection, including Cianciolo (2000), Schiro (1997), Hunsader (2004) and Van den Heuvel-Panhuizen and Elia (2012). Geometry concepts have proven challenging for young students, but their difficulties may stem, in part, from inadequate teacher training and professional development (Chard, Baker & Clarke, 2008; Clements & Sarama, 2000) which lead to misconceptions (Inan & Dogan-Temur, 2010; Oberdorf & Taylor-Cox, 1999). Using picture books in teacher training may be an inviting way for early childhood teachers to enhance their own knowledge. We will examine the literature for guidance on incorporating children’s literature into teacher training. In closing we will outline a comprehensive, multi-pronged agenda for best instructional practices for selection and use of children’s books in mathematics activities and for teacher training.